(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Here we present the efficacies of Murraya koenigii leaves extract as natural antibacterial agents by the ability to inhibit the growth of Escherichia coli and Staphylococcus aureus. The antibacterial activities of formulated liquid hand soap with different concentrations (10, 30 and 50 mg/mL) of M. koenigii extracts were determined by paper disc diffusion method. M. koenigii leaves extract at 10 mg/mL concentration had the ability to inhibit the growth of both test microorganisms. Whereas, for liquid hand soap formulated with 10, 30 and 50 mg/mL M. koenigii extracts, inhibition zones were observed on S. aureus assay plates but not on E. coli. Hence, the results suggested that liquid hand soap containing M. koenigii extract had therapeutic potentials to prevent spread of skin diseases caused by S. aureus.